Surface modification study of CaO-Al2O3-SiO2-Fe2O3 base system high temperature phase reconstruction - Yang, Huanyin; Guo, Hongli; Sun, Hongjuan; Peng, Tongjiang (Frontiers in Materials, 2023)
The fly ash was used as raw material to prepare glass ceramic base body, on which a layer of glaze slurry was applied, then, the complex was successfully prepared by sintering at 1180 °C through single-sinter process. Influences of quartz sand content on crystal phase evolution, physical–mechanical properties, and surface morphology of products were studied systematically. Finally, an opaque glaze with 15 wt% quartz sand fitting on glass ceramic base body had been produced, exhibiting a unique main phase, mullite, which ensured a significant Vickers microhardness of 8.1 GPa, improving the mechanical properties of solid waste glass ceramic base body. It was also found that the water absorption of the product was .66%, which greatly enhanced the waterproof function of the base surface. The complex products developed in this study were expected to be used as building decoration materials and provided new ideas for effective reuse of other similar solid wastes.